Discovery of an evodiamine derivative for PI3K/AKT/GSK3β pathway activation and AD pathology improvement in mouse models - Pang, Shuo; Li, Siyuan; Cheng, Hanzeng; Luo, Zhuohui; Qi, Xiaolong; Guan, Feifei; Dong, Wei; Gao, Shan; Liu, Ning; Gao, Xiang; Pan, Shuo; Zhang, Xu; et al. (Frontiers in Molecular Neuroscience, 2023)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive neurodegeneration and cognitive decline. Evodiamine, a main component in Chinese medicine, was found to improve cognitive impairment in AD model mice based on several intensive studies. However, evodiamine has high cytotoxicity and poor bioactivity. In this study, several evodiamine derivatives were synthesized via heterocyclic substitution and amide introduction and screened for cytotoxicity and antioxidant capacity. Under the same concentrations, compound 4c was found to exhibit lower cytotoxicity and higher activity against H2O2 and amyloid β oligomers (AβOs) than evodiamine in vitro and significantly improve the working memory and spatial memory of 3 x Tg and APP/PS1 AD mice. Subsequent RNA sequencing and pathway enrichment analysis showed that 4c affected AD-related genes and the AMPK and insulin signaling pathways. Furthermore, we confirmed that 4c recovered PI3K/AKT/GSK3β/Tau dysfunction in vivo and in vitro. In conclusion, 4c represents a potential lead compound for AD therapy based on the recovery of PI3K/AKT/GSK3β pathway dysfunction.